Language System, Translation Technique, and Textual Tradition in the Peshitta of Kings - Dyk, J. W. (Monographs of the Peshitta Institute Leiden, 2013)
In this MPIL volume, Janet Dyk and Percy van Keulen implement computer science, linguistic analysis, and text-historical insights in treating the differences between the Hebrew and Syriac versions of Kings. Applying the distinct disciplines helped in arriving at a more balanced assessment of the nature and provenance of the deviations observed